2015
DOI: 10.1177/0961203315570165
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CCP antibodies as a marker of rhupus

Abstract: Anti-CCP antibodies as a marker of rhupus Sir,We have read with interest the works on rhupus, a clinical condition characterized by the coexistence of rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE), recently published in Lupus. 1,2 These publications prompted us to investigate the prevalence and characteristics of rhupus in our cohort of patients with SLE, 3,4 fulfilling international classification criteria. 5,6 This was a cross-sectional analytical study conducted in 377 Colombian patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…Patients with rhupus syndrome have been reported to have ANA, dsDNA, RF, and anti-CCP antibodies [ 16 ]. In the present study, the positive rates of anti-CCP and titer of anti-CCP were significantly higher in rhupus patients than in the SLE with arthropathy group, which agrees with some previous studies [ 17 , 18 ]. Anti-CCP antibodies have been shown to play an essential diagnostic role in patients with rhupus symptom and may increase the risk of erosive arthritis in RS patients [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…Patients with rhupus syndrome have been reported to have ANA, dsDNA, RF, and anti-CCP antibodies [ 16 ]. In the present study, the positive rates of anti-CCP and titer of anti-CCP were significantly higher in rhupus patients than in the SLE with arthropathy group, which agrees with some previous studies [ 17 , 18 ]. Anti-CCP antibodies have been shown to play an essential diagnostic role in patients with rhupus symptom and may increase the risk of erosive arthritis in RS patients [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…The presence of anti-CCP antibodies is considered highly specific for RA, but can also be found in other conditions, including SLE, where frequencies from 2–17% have been described [9, 32, 4551]. Whether or not there is a true association between a positive anti-CCP test and erosive arthritis in SLE remains an open question, as several investigators have reported this [9, 4650], whereas others have not [31, 45]. Kakumanu et al reported a prevalence of 17% for anti-CCP positivity among 329 patients with SLE but that citrulline-dependent anti-CCP was mainly found in patients with erosive arthritis, which involved only 26 patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RTX therapy has been effective in SS (38) and cytokine levels show a significant decrease after therapy (39). RA may also be associated with PolyA (2) and its coexistence with SLE is known as Rhupus, with a prevalence as high as 10% in SLE patients (40,41). RTX has been shown to improve the clinical presentation for both entities (42).…”
Section: Introductionmentioning
confidence: 99%